Pharmaceutical pollution in a wastewater-impacted coastal ecosystem - Raiko Rafeeq; Erinn K. Richmond; Wei Wen Wong; Daniel Cerveny; Tomas Brodin; Minna Saaristo; Michael R. Grace; Perran Cook; Bob B.M. Wong (Environmental Pollution, 2026)

Implications of sulphide toxicity for seed-based seagrass restoration - Laney Callahan; Rhys A. Coleman; Lawrence Webb; Perran LM. Cook; Daniel Ierodiaconou; Craig DH. Sherman (Marine Environmental Research, 2026)

Novel commensal rhizobacteria isolated from field-grown canola plants - Christopher Blake; Storme de Scally; John Pascoe; Atharva Bhide; Aysha L. Sezmis; Perran L.M. Cook; Vanessa N.L. Wong; Harsh Raman; Michael J. McDonald (Biocatalysis and Agricultural Biotechnology, 2026)

Mechanisms and factors controlling greenhouse gases production in agricultural drains and ponds - Justice Obinna Osuoha; Michael Tolj; Anna Lintern; Robert Sargent; Joachim Mohn; Perran L.M. Cook; Wei Wen Wong (Water Research, 2026)

Dissimilatory nitrate reduction to ammonium driven by iron tolerant Lutibacter in coastal sediments - Maha Alharbi; Thanh Nguyen-Dinh; Wei Wen Wong; Pok Man Leung; Adam J. Kessler; Chris Greening; Perran L.M. Cook (Science of The Total Environment, 2026)

Surplus nutrient exports differ between irrigated and high-rainfall agricultural catchments: a tale of two catchments in South East Australia - Robert Sargent; Wei Wen Wong; Andrew W. Western; Perran Cook; Anna Lintern (Journal of Hydrology, 2025)

Correlations between catchment-scale farm infrastructure densities and stocking rate to stream nutrient concentrations in dairy-dominant catchments - Jonah Lee Bas; Andrew W. Western; Robert Sargent; Wei Wen Wong; Perran Cook; Anna Lintern (Journal of Environmental Management, 2025)

Identifying resilient areas for seagrass restoration by integrating suitability modelling and climate forecasting - Oliver Dalby; Mary A. Young; Emma L. Jackson; Yi Mei Tan; Rhys A. Coleman; Kathy Cinque; Peter Yeates; Perran Cook; Peter I. Macreadie; Daniel Ierodiaconou; Craig D.H. Sherman (Estuarine, Coastal and Shelf Science, 2025)

Carbon-based nanomaterials enhance the growth of cable bacteria in brackish sediments - Michaela M.H. Wawryk; Silvia Hidalgo-Martinez; Filip J.R. Meysman; Rico F. Tabor; Perran L.M. Cook (Science of The Total Environment, 2024)

Spatio-temporal patterns in the biomass, species composition and nitrogen content of drift macroalgae in an urbanised coastal embayment - Juan Manuel Valero-Rodriguez; Tim Dempster; Wei Wen Wong; John A. Lewis; Perran L. M. Cook; Stephen E. Swearer (Journal of Applied Phycology, 2024)
Understanding spatio-temporal variability in the production of drift macroalgae is useful for monitoring and assessing the influence of local anthropogenic nutrient sources on coastal ecosystems. In this study we: (1) assessed how the drift macroalgal community composition and biomass have changed over a 22-year period in Port Phillip Bay (a large coastal embayment in Victoria, Australia); and (2) measured the amount of accumulated nitrogen in drift macroalgae and the contribution of anthropogenic nitrogen sources through isotopic analysis. The surveys revealed little overlap in species composition (<13%) and a significant decrease in standing stock biomass (from 631 to 49 g m -2 ) between surveys (1995/1996 and 2017/2018). This was associated with a high degree of turnover (β-diversity) at the genus level between surveys (mean – 0.53), resulting in distinct communities at all sites, particularly among red algal genera. In addition, the occurrence of ephemeral macroalgal blooms and a semi-perennial mat of the red macroalga Botryocladia sonderi at 10-15 m depth at locations close to nutrient sources indicate drift macroalgae are important nutrient accumulators in the bay. Isotopic analysis revealed a high contribution of anthropogenic-derived nitrogen (δ 15 N > 17‰ and ~ 3% N content) at depths and locations close to nutrient sources, particularly at times of the year when large wastewater discharges occur. Harvesting of drift macroalgae could be a cost-effective solution for offsetting nitrogen inputs from anthropogenic sources, but it will be important to first investigate whether harvesting results in negative impacts to associated fauna or nutrient cycling.

Electrogenic sulfur oxidation by cable bacteria in two seasonally hypoxic coastal systems - Laurine D.W. Burdorf; Perran L.M. Cook; Elizabeth K. Robertson; Anton Tramper; Silvia Hidalgo-Martinez; Diana Vasquez-Cardenas; Sairah Y. Malkin; Filip J.R. Meysman (Estuarine, Coastal and Shelf Science, 2024)

Stable isotopes of nitrate (δ15N and δ18O) as functional indicators of nitrogen processing in constructed wetlands - Keryn Roberts; Michael Grace; Perran Cook; Dirk Erler; Wei Wen Wong (Science of The Total Environment, 2023)

Pulses of labile carbon cause transient decoupling of fermentation and respiration in permeable sediments - Philipp A. Nauer; Adam J. Kessler; Puspitaningsih Hall; Maria Elena Popa; Sophie ten Hietbrink; Tess Hutchinson; Wei Wen Wong; Karl Attard; Ronnie N. Glud; Chris Greening; Perran L. M. Cook (Limnology and Oceanography, 2023)
Dihydrogen (H 2 ) is an important intermediate in anaerobic microbial processes, and concentrations are tightly controlled by thermodynamic limits of consumption and production. However, recent studies reported unusual H 2 accumulation in permeable marine sediments under anoxic conditions, suggesting decoupling of fermentation and sulfate reduction, the dominant respiratory process in anoxic permeable marine sediments. Yet, the extent, prevalence and potential triggers for such H 2 accumulation and decoupling remain unknown. We surveyed H 2 concentrations in situ at different settings of permeable sand and found that H 2 accumulation was only observed during a coral spawning event on the Great Barrier Reef. A flume experiment with organic matter addition to the water column showed a rapid accumulation of hydrogen within the sediment. Laboratory experiments were used to explore the effect of oxygen exposure, physical disturbance and organic matter inputs on H 2 accumulation. Oxygen exposure had little effect on H 2 accumulation in permeable sediments suggesting both fermenters and sulfate reducers survive and rapidly resume activity after exposure to oxygen. Mild physical disturbance mimicking sediment resuspension had little effect on H 2 accumulation; however, vigorous shaking led to a transient accumulation of H 2 and release of dissolved organic carbon suggesting mechanical disturbance and cell destruction led to organic matter release and transient decoupling of fermenters and sulfate reducers. In summary, the highly dynamic nature of permeable sediments and its microbial community allows for rapid but transient decoupling of fermentation and respiration after a C pulse, leading to high H 2 levels in the sediment.

Recovery of denitrification and dissimilatory nitrate reduction to ammonium following reoxygenation of sediments from a periodically hypoxic temperate lagoon - Keryn L. Roberts; Wei Wen Wong; Jeff Shimeta; Adam J. Kessler; Perran L. M. Cook (Limnology and Oceanography, 2022)
Eutrophication and stratification events have increased the incidences of hypoxia and anoxia in coastal environments. The depletion of oxygen in these environments can lead to a shift in biogeochemical processes such as denitrification and dissimilatory nitrate reduction to ammonium (DNRA). The balance between denitrification and DNRA is critical because denitrification leads to a loss of bioavailable nitrogen and DNRA maintains it within the system. This study examined the effects of reoxygenation on denitrification and DNRA in sediments collected from a periodically hypoxic system (Gippsland Lakes, Australia) and subjected to experimental hypoxia using a modified 15 N‐isotope pairing technique. For freshly collected sediments, the ratio of denitrification : DNRA was generally 1. Profiles of 15 N‐N 2 and accumulation in these experiments showed denitrification and DNRA generally only took place in the surface ~ 2 cm of sediment. Prolonged experiments with reoxygenated sediments showed a decrease in the denitrification : DNRA to

Nitrogen and oxygen isotopomeric constraints on the sources of nitrous oxide and the role of submarine groundwater discharge in a temperate eutrophic salt‐wedge estuary - Wei Wen Wong; Moritz F. Lehmann; Thomas Kuhn; Caitlin Frame; Seng Chee Poh; Ian Cartwright; Perran L.M. Cook (Limnology and Oceanography, 2021)
Estuaries have been identified as sources of nitrous oxide (N 2 O) emissions to the atmosphere but questions remain as to which production pathway(s) govern the oversaturation of N 2 O observed in most estuaries worldwide. Here, we use a suite of nitrate and N 2 O isotopes, as well as the 15 N site preference signatures of N 2 O to assess (1) the relative importance of different N 2 O production pathways in a eutrophic groundwater‐impacted salt‐wedge estuary and the aquifers underlying the estuary and (2) the influence of groundwater input on the overall N 2 O saturation in the estuary. This is one of the few studies to examine the effect of groundwater–surface water interaction on N 2 O cycling using N 2 O isotopes. The site preference values of N 2 O in the deep aquifer below the estuary were distinctive (83‰ ± 25‰) and were much higher than in either surface water (21‰ ± 6‰) or shallow groundwater (44‰ ± 8‰), suggesting the influence of multiple biotic and/or abiotic processes which proceed through multiple cycles, and/or the occurrence of a yet unidentified N 2 O production pathway. Isotope endmember considerations revealed that nitrifier‐denitrification was the major N 2 O production pathway within the shallow aquifer whereas within the estuarine water column, N 2 O saturation was governed by chemodenitrification and discharge of N 2 O‐laden submarine groundwater. Our study not only emphasizes the substantial, yet often underappreciated role of submarine groundwater discharge in estuarine N 2 O budgets, but also highlights the need to reevaluate the importance of the noncanonical denitrification pathways (i.e., chemodenitrification and nitrifier‐denitrification) in controlling the overall N 2 O production from estuarine and groundwater environments.

Biogeochemical attenuation of nitrate in a sandy subterranean estuary: Insights from two stable isotope approaches - Wei Wen Wong; Andrew Applegate; Seng Chee Poh; Perran L. M. Cook (Limnology and Oceanography, 2020)
The role of permeable sediments and subterranean estuaries as coastal nutrient filters is a question of key interest, particularly in areas with high nitrogen loadings. Here, we evaluated the effectiveness of a sandy subterranean estuary in cycling and removing nitrate using stable isotopes of N and O at natural (δ 15 N‐NO 3 − and δ 18 O‐NO 3 − ) and enriched levels ( 15 N). Isotopes were used in conjunction with flow through reactors under anoxic conditions to quantify (1) the overall enrichment factor ( 15 ε) of nitrate removal processes which was then applied to estimate the in situ percentage of nitrate removal within the subterranean estuary and (2) the potential rates of denitrification, dissimilatory nitrate reduction to ammonium, and anammox. We found that 15 ε varied between −24 and −34‰ and were positively correlated with nitrate concentrations and the percentage of organic carbon added to the sediments. Using these 15 ε values in a Rayleigh distillation model resulted in an estimated average of 34% ± 14% nitrate removal within the subterranean estuary, less than half of the percentage estimated using the nitrate‐salinity mixing model (66% ± 28%). Denitrification was the most dominant nitrate removal pathway within the subterranean estuary with potential rates among the highest denitrification rates reported for both permeable and cohesive sediments. The contribution of dissimilatory nitrate reduction to ammonium showed significant seasonal variation while the rates of anammox were consistent throughout the study. We suggest that the spatial shift of the subterranean estuary is the most likely explanation for the seasonal differences in the rates of denitrification and dissimilatory nitrate reduction to ammonium.

Editorial: Facing Marine Deoxygenation - Arthur Capet; Perran Cook; Emilio Garcia-Robledo; Babette Hoogakker; Aurélien Paulmier; Christophe Rabouille; Raquel Vaquer-Sunyer (Frontiers in Marine Science, 2020)

Cable bacteria promote DNRA through iron sulfide dissolution - Adam J. Kessler; Michaela Wawryk; Ugo Marzocchi; Keryn L. Roberts; Wei Wen Wong; Nils Risgaard‐Petersen; Filip J. R. Meysman; Ronnie N. Glud; Perran L. M. Cook (Limnology and Oceanography, 2019)
Cable bacteria represent a newly discovered group of filamentous microorganisms, which are capable of spatially separating the oxidative and reductive half‐reactions of their sulfide‐oxidizing metabolisms over centimeter distances. We investigated three ways that cable bacteria might interact with the nitrogen (N) cycle: (1) by reducing nitrate through denitrification or dissimilatory nitrate reduction to ammonium (DNRA) within their cathodic cells; (2) by nitrifying ammonium within their anodic cells; and (3) by indirectly affecting denitrification and/or DNRA by changing the Fe 2+ concentration in the surrounding sediment. We performed 15 N labeling laboratory experiments to measure these three processes using cable bacteria containing sediments from the Yarra River, Australia, and from Vilhelmsborg Sø, Denmark. Our results revealed that in the targeted systems, cable bacteria themselves did not perform significant rates of denitrification, DNRA, or nitrification. However, cable bacteria exhibited an important indirect effect, whereby they increased the Fe 2+ pool through iron sulfide dissolution. This elevated availability of Fe 2+ significantly increased DNRA and in some cases decreased denitrification. Thus, cable bacteria presence may affect the relative importance of DNRA in sediments and thus the extent by which bioavailable nitrogen is lost from the system.

Delayed timing of successful spawning of an estuarine dependent fish, black bream Acanthopagrus butcheri - Gregory P. Jenkins; Julia A. Kent; Ryan J. Woodland; Fiona Warry; Stephen E. Swearer; Perran L. M. Cook (Journal of Fish Biology, 2018)
In this paper, we investigate the period of successful spawning for black bream Acanthopagrus butcheri , an obligate estuarine species in southern Australia that typically spawn in spring and early summer. However, back‐calculated spawning dates of juveniles sampled in Gippsland Lakes, Victoria from February to May 2016 indicated that spawning was concentrated over a short period in the Austral mid‐summer (January), with a second spawning in late summer and early autumn (late February–early March). Ichthyoplankton sampling in the tributary estuaries from October to early December collected substantial numbers of fish larvae, dominated by gobiids, eleotrids and retropinnids of freshwater origin, but no A. butcheri . The lack of A. butcheri larvae was consistent with the delayed successful spawning indicated by juvenile otolith data. Freshwater flows declined from late winter to summer, with consistent salinity stratification of the water column. Dissolved oxygen (DO) concentrations were generally very low below the halocline. These conditions may have delayed the upstream spawning migration of adults or may have been unsuitable for survival of eggs and newly‐hatched larvae. Longer‐term predictions for climate change in southern Victoria, including the Gippsland Lakes region, are for lower winter–spring freshwater flows, potentially benefiting the reproductive success of A. butcheri through high water‐column stratification, but only if DO concentrations are not compromised by a lack of high winter flows needed to flush low DO water from the system.

The balance between nitrogen fixation and denitrification on vegetated and non‐vegetated intertidal sediments - Douglas G. Russell; F. Y. Warry; Perran L. M. Cook (Limnology and Oceanography, 2016)

Deep dynamic pools of phosphorus in the sediment of a temperate lagoon with recurring blooms of diazotrophic cyanobacteria - Todd R. Scicluna; Ryan J. Woodland; Yafei Zhu; Michael R. Grace; Perran L. M. Cook (Limnology and Oceanography, 2015)
The storage and release of phosphorus by sediments can act as an important control on the formation of noxious blooms of cyanobacteria in lakes and estuaries. Here we studied the uptake and release of phosphorus associated with iron oxides within sediments of a lagoon system affected by recurring summer blooms of the cyanobacterium Nodularia spumigena . Using an ascorbate extraction, we observed deep pools of iron oxide associated phosphorus (P) at concentrations of ∼5 μ mol g −1 dry sed to a depth of ∼20 cm. This pool rapidly decreased with the onset of water column anoxia, leading to an integrated release of ∼300 mmol of phosphorus m −2 of sediment over 3.5 months. Scaling this flux over the periodically anoxic area of the lake and over the period of an N. spumigena bloom (November–December 2011) gave a broad mass balance agreement with the increase in total phosphorus within the water column and exported from the lagoon. Over this period we estimated that P release from the sediment would have allowed ∼130–187 tonnes of nitrogen to be fixed which agrees with previous estimates of nitrogen fixation. Upon reoxygenation of the water column, a regeneration of the deep iron oxide associated phosphorus pool was observed. This deep dynamic pool of phosphorus was most likely mediated by the burrowing activity of the polychaete Capitella capitata which was observed at the study site. This study underscores the potential importance of sediments colonized by deeply irrigating fauna to become a significant source of phosphorus during water column anoxia.

Nitrogen loads explain primary productivity in estuaries at the ecosystem scale - Ryan J. Woodland; James R. Thomson; Ralph Mac Nally; Paul Reich; Victor Evrard; Fiona Y. Wary; Jeffrey P. Walker; Perran L. M. Cook (Limnology and Oceanography, 2015)
Increased nutrient loads stimulate estuary primary productivity and can alter the structure and function of biological communities within estuaries, particularly when producer groups respond differently to changes in nutrient availability. Here, the relative influence of riverine inputs of nitrogen and phosphorus were compared to determine their contribution to estuarine primary producers at large spatial scales. Indices of demersal (extent of macroalgae relative to other vegetation, total shallow water area vegetated) and planktonic (seasonally averaged chlorophyll concentration) primary producer communities were derived at whole‐of‐ecosystem scales in 14 estuaries dispersed across a longitudinal gradient using aerial imaging, underwater videography and in situ monitoring. A model selection framework was used to relate annual nutrient loads (total nitrogen [TN], dissolved inorganic nitrogen [DIN], total phosphorus [TP]), sediment loads (TSS), molar stoichiometric load ratios (TN M : TP M ), and estuary water residence times to the demersal and planktonic indices. Dissolved inorganic nitrogen was the best predictor of the extent of macroalgae, total vegetation coverage, and the concentration of planktonic chlorophyll. Rapid increases in all three indices occurred at inorganic nitrogen loads of ∼ 5–10 Mg km −2 yr −1 . There was some evidence that TN M : TP M , TP and TSS loads were informative model covariates. Relative to DIN loads, TP loads were a poor predictor of the macroalgal and planktonic indices. These findings underscore the critical role of catchment‐derived nitrogen in contributing to producer communities at the whole‐of‐ecosystem scale and support the growing consensus that nitrogen loads (in addition to phosphorus) must be managed to effectively alleviate eutrophication in estuaries.

Sources and fate of nitrate in a groundwater‐fed estuary elucidated using stable isotope ratios of nitrogen and oxygen - Wei Wen Wong; Michael R. Grace; Ian Cartwright; Perran L. M. Cook (Limnology and Oceanography, 2014)
We used δ 15 N‐nitrate (NO − 3 ) and δ 18 O‐NO − 3 to unravel the provenance and fate of NO − 3 in a groundwater‐fed estuary. A total of 13 monthly and two time series surveys were undertaken in the Werribee River estuary near Melbourne, Australia. The different survey timescales provided a comprehensive evaluation of the hydrological effects on the biogeochemistry of NO − 3 , which accounted for tidal variability and episodic runoff events. The distribution of δ 15 N and δ 18 O of the estuarine NO − 3 along a mixing line between shallow and deep groundwater provided strong evidence for the predominance of groundwater‐derived NO − 3 in the estuary. During dry periods when water residence time in the estuary was extended, shallow groundwater contributed 60% to 76% of the NO − 3 (calculated from δ 15 N‐NO − 3 and δ 18 O‐NO − 3 ) to the estuary, and assimilation removed ∼ 70% of this groundwater‐derived NO − 3 . During wet periods, deep groundwater provided more (62%) NO − 3 than shallow groundwater, and there was no indication of NO − 3 consumption. Occasional sources of NO − 3 , which were also reflected by their δ 15 N‐NO − 3 and δ 18 O‐NO − 3 values, included NO − 3 from nitrification and sewage‐derived NO − 3 particularly at the bay entrance to the estuary. Greater emphasis should be placed upon the role of groundwater as a substantial NO − 3 end member when assessing NO − 3 biogeochemistry using methods relying on the dual isotopic composition of NO − 3 .

Pore‐water exchange driven by tidal pumping causes alkalinity export in two intertidal inlets - Peter A. Faber; Victor Evrard; Ryan J. Woodland; Ian C. Cartwright; Perran L. M. Cook (Limnology and Oceanography, 2014)
Carbon (C) and alkalinity export from two adjacent intertidal inlets with different terrestrial inputs was investigated. One inlet receives a small creek from an agriculturally dominated catchment, leading to the input of terrestrially sourced material, whereas the other is relatively isolated from terrestrial inputs. Using time‐series measurements, we calculated the total advective exchange of dissolved organic C (DOC; 0–25 mmol m ‒2 d ‒1 ), dissolved inorganic C (DIC; 130–450 mmol m ‒2 d ‒1 ), total alkalinity (TA; 46–310 mmol m ‒ d ‒1 ), and the nutrients nitrate (1.0–1.1 mmol m ‒2 d ‒1 ), ammonia (0.0043–0.10 mmol m ‒2 d ‒1 ), and phosphorus (0.016–0.25 mmol m ‒2 d ‒1 ). Radon‐222 ( 222 Rn) data indicated that pore‐water exchange played an important part in controlling C export from the sediment as an advective flux. The residence time of pore water within both inlets was ~ 6.6–7.4 h, indicating that pore‐water exchange is driven by tidal pumping. The inlet with the greater amount of terrestrial inputs exported much more TA (310 vs. 46 mmol m ‒2 d ‒1 ), suggesting that the extent of land‐to‐sea connectivity influences how C is exported. We hypothesize that this is due to the increased input of iron (Fe) from terrestrial sources, which fosters net TA production through the burial of reduced sulfur species as Fe sulfides. A simple mass balance showed that the TA fluxes observed over 24 h were higher than could be sustained continuously with Fe input from the catchment (0.49 mmol Fe m ‒2 d ‒1 ), meaning that the observed TA fluxes could not be sustained on long timescales. It is most likely that there are periods of net reduction and net oxidation in response to wave action and calm conditions, highlighting the importance of long‐term monitoring over different seasons and weather patterns to obtain representative budgets.

Processes and Drivers of Nitrogen Removal in Stormwater Biofiltration - Emily G. I. Payne; Tim D. Fletcher; Perran L. M. Cook; Ana Deletic; Belinda E. Hatt (Critical Reviews in Environmental Science and Technology, 2014)

Dynamics of groundwater‐derived nitrate and nitrous oxide in a tidal estuary from radon mass balance modeling - Wei Wen Wong; Michael R. Grace; Ian Cartwright; M. Bayani Cardenas; Peter B. Zamora; Perran L. M. Cook (Limnology and Oceanography, 2013)
We monitored submarine groundwater discharge (SGD) into the Werribee Estuary, Australia, using both chemical and physical methods. SGD occurred at hotspots where 222 Rn persisted through a 12 month survey period. A significant correlation between 222 Rn and ( r 2 = 0.8, p 222 Rn and N 2 O ( r 2 = 0.6, p 222 Rn hotspot, and much higher and N 2 O concentrations in groundwater relative to surface water suggest that elevated and N 2 O concentrations in the estuary were derived from SGD. Two sampling campaigns over 24 h revealed that variations of 222 Rn,, and N 2 O were controlled by tide‐induced hydraulic‐head gradient fluctuations and, possibly to a much lesser extent, by tidal pumping and density‐driven convection. A two‐box 222 Rn mass‐balance model was used to calculate the rate of SGD into two different layers across the pycnocline of the estuary. A higher total groundwater discharge rate of 0.12 ± 0.09 m d −1 was observed in the surface layer during ebb tide compared with 0.10 ± 0.08 m d −1 during flood tide. Fluxes of groundwater‐derived and N 2 O were higher than the riverine flux at baseflow by more than 30 fold and 20 fold, respectively. SGD derived fluxes exceeded the mean annual riverine and TN fluxes by a factor of ∼ 5 and ∼ 3 respectively. SGD‐derived N 2 O fluxes were 170 µmol m −2 d −1 , which are among the highest N 2 O fluxes observed in estuaries.

Hypoxic events stimulate nitrogen recycling in a shallow salt‐wedge estuary: The Yarra River estuary, Australia - Keryn L. Roberts; Vera M. Eate; Bradley D. Eyre; Daryl P. Holland; Perran L. M. Cook (Limnology and Oceanography, 2012)
The Yarra River estuary is a salt‐wedge estuary prone to periods of stratification‐induced anoxia and hypoxia (O 2 −1 ) during low‐flow events. Nitrate reduction pathways were examined using the 15 N isotope pairing technique in intact sediment cores, emulating in situ conditions, to evaluate the fate of NO during changing oxygen conditions. Water‐column concentrations of dissolved inorganic carbon (DIC), O 2 , NH, and NO x (NO + NO) were also measured to examine any deviation from conservative behavior (denoted Δ) in response to oxygen variability within the estuary. The estuary was a source of NH in the anoxic bottom waters. Whole‐system estimates using deviations from conservative behavior and core incubations were in good agreement and showed that NH was regenerated more efficiently relative to DIC under hypoxic conditions. For the whole system, mean ΔDIC : ΔNH ratios under oxic (85 ± 33) and hypoxic (20 ± 3) conditions were significantly different. The more‐efficient NH regeneration during hypoxia was attributed to rapid mineralization rates and cessation of nitrification; dissimilatory nitrate reduction to ammonium (DNRA) was not a significant contributor. Unexpectedly, the denitrification : DNRA ratio was significantly higher under hypoxic conditions, with denitrification contributing 99.1% ± 0.3% of total nitrate reduction. DNRA rates were significantly higher during oxic conditions (123.5 ± 30.7 µmol m −2 h −1 ) when compared with rates during hypoxia (0.6 ± 0.1 µmol m −2 h −1 ). The increase in DNRA in the presence of oxygen was attributed to the alleviation of NO limitation during these conditions.

The “salt wedge pump”: Convection‐driven pore‐water exchange as a source of dissolved organic and inorganic carbon and nitrogen to an estuary - Isaac R. Santos; Perran L. M. Cook; Louissa Rogers; Jason de Weys; Bradley D. Eyre (Limnology and Oceanography, 2012)
Hypoxia and anoxia in coastal waters have typically been explained by the respiration of sinking organic matter associated with nutrient over‐enrichment and phytoplankton blooms. Here, we assess whether submarine groundwater discharge and seawater recirculation in sediments can explain widespread chemical anomalies, including low dissolved oxygen, in salt wedge estuaries. We rely on high‐resolution radon (a natural groundwater and pore‐water tracer), and dissolved carbon concentrations and stable isotope observations in the Yarra River estuary in Melbourne, Australia. Radon was highly enriched within the salt wedge, demonstrating enhanced pore‐water exchange at this area. We use the term “salt wedge pump” to describe convection‐driven advective pore‐water exchange at the sediment–water interface during the upstream propagation of the salt wedge. Radon‐derived convection‐driven pore‐water exchange rates within the salt wedge were estimated at 2.8 cm d −1 , a value equivalent to 2.4% of the total river freshwater runoff to the estuary. Pore‐water exchange led to pulsed dissolved inorganic carbon (DIC) and ammonium fluxes ∼ 10‐fold higher than measured diffusive fluxes. In contrast, diffusive sediment oxygen uptake was 5‐fold higher than oxygen uptake related to advective pore‐water exchange. Estimated fluxes, associated with the nonconservative DIC, δ 13 C‐DIC, and ammonium behavior within the estuary support convective pore‐water exchange as a major source of DIC and ammonium to the estuary, but not of dissolved organic carbon, nitrate, dissolved organic nitrogen, and anoxia. Accounting for seawater recirculation in sediments may help reconcile unbalanced carbon and nitrogen budgets in several coastal systems.

Quantifying denitrification in rippled permeable sands through combined flume experiments and modeling - Adam J. Kessler; Ronnie N. Glud; M. Bayani Cardenas; Morten Larsen; Michael F. Bourke; Perran L. M. Cook (Limnology and Oceanography, 2012)
We measured denitrification in permeable sediments in a sealed flume tank with environmentally representative fluid flow and solute transport behavior using novel measurements. Numerical flow and reactive transport models representing the flume experiments were implemented to provide mechanistic insight into the coupled hydrodynamic and biogeochemical processes. There was broad agreement between the model results and experimental data. The model showed that the coupling between nitrification and denitrification was relatively weak in comparison to that in cohesive sediments. This was due to the direct advective transport between anoxic pore water and the overlying water column, and little interaction between the mostly oxic advective region and the underlying anoxic region. Denitrification was therefore mainly fueled by nitrate supplied from the water column. This suggests that the capacity of permeable sediments with nonmigratory ripples to remove bioavailable nitrogen from coastal ecosystems is lower than that of cohesive sediments. We conclude that while experimental measurements provide a good starting point for constraining key parameters, reactive transport models with realistic kinetic and transport parameters provide critical insight into biogeochemical processes in permeable sediment that are difficult to experimentally evaluate.

Effect of a flood event on the dynamics of phytoplankton and biogeochemistry in a large temperate Australian lagoon - Perran L. M. Cook; Daryl P. Holland; Andrew R. Longmore (Limnology and Oceanography, 2010)
In episodically driven estuaries, nutrient delivery is typically confined to sporadic flow events, followed by intense biogeochemical recycling of nutrients. We document the response of a temperate lagoon system with episodic winter‐ or spring‐dominated catchment inflows (Gippsland Lakes, southeast Australia) to a flood event. High winter inflows resulted in high surface‐water concentrations of inorganic nitrogen (IN; NO 2 − + NO 3 − + NH 4 + ) relative to reactive phosphorus (RP) with an IN :RP ratio > 100. This resulted in a rapid diatom and dinoflagellate bloom, which collapsed as water column nutrients were exhausted. Increased carbon delivery to the sediment stimulated benthic respiration and depleted bottom‐water oxygen, which led to a large release of RP from the sediments, decreasing the IN :RP ratio in the bottom water to ~6. Strong stratification of the water column allowed the accumulation of RP in the bottom water over spring and into summer. Mixing of RP from the bottom water over summer triggered the development of a Nodularia spumigena Mertens bloom. As such, the nutrient supply for the Nodularia bloom was through a biogeochemical filter that strongly favored N 2 ‐fixing cyanobacterial blooms by reducing IN :RP ratios through a combination of sediment denitrification and release of stored phosphorus from within the sediment. These observations lead us to the paradoxical conclusion that high nitrogen loading over winter contributed to severe nitrogen limitation over summer, and highlight the importance of controlling both nitrogen and phosphorus loading to estuaries.

Benthic solute exchange and carbon mineralization in two shallow subtidal sandy sediments: Effect of advective pore‐water exchange - Perran L. M. Cook; Frank Wenzhöfer; Ronnie N. Glud; Felix Janssen; Markus Huettel (Limnology and Oceanography, 2007)
We conducted four field campaigns to evaluate benthic O 2 consumption and the effect of advective pore‐water flow in nearshore permeable sediments in the North Sea and Baltic Sea. Advective pore‐water transport had a marked effect on the benthic exchange of O 2 and TCO 2 in benthic chamber incubations, with the rates of exchange increasing by a factor of up to 2.5 when imposing flushing rates of 100‐300 L m −2 d −1 , compared to settings with diffusive exchange only. Estimates of in situ exchange rates using oxygen penetration and volumetric O 2 consumption and TCO 2 production rates were within the range measured in the chambers. The contribution of advection to solute exchange was highly variable and dependent on sediment topography. Advective processes also had a pronounced influence on the in situ distribution of O 2 within the sediment, with characteristic two‐dimensional patterns of O 2 distribution across ripples, and also deep subsurface O 2 pools, being observed. Mineralization pathways were predominantly aerobic when benthic mineralization rates were low and advective pore‐water flow high as a result of well‐developed sediment topography. By contrast, mineralization proceeded predominantly through sulfate reduction when benthic mineralization rates were high and advective pore‐water flow low as a result of poorly developed topography. Previous studies of benthic mineralization in shallow sandy sediments have generally ignored these dynamics and, hence, have overlooked crucial aspects of permeable sediment function in coastal ecosystems.

Bacterial community shifts in organically perturbed sediments - Andrew Bissett; Chris Burke; Perran L. M. Cook; John P. Bowman (Environmental Microbiology, 2007)
Summary Bacterial abundance, diversity and sediment function were investigated in organically perturbed sediments under Tasmanian salmon ( Salmo salar ) farms and adjacent reference sites. Bacterial numbers increased as farming and organic loading progressed through the farm stocking cycle and declined during the fallow period, although not to prestocking levels. Bacterial numbers ranged between approximately 2 × 10 8 and 3 × 10 9 cells per gram of sediment and were higher at cage sites than reference sites. Microelectrode and respiration data also demonstrated a clear effect of organic loading on sediments. Denaturing gradient gel electrophoresis (DGGE) showed that bacterial communities shifted both in response to farm loading and its cessation. A seasonal effect on microbial communities was also evident. Although bacterial communities did shift again during the fallowing period, this shift was not necessarily a return to preloading communities. The complexity of community shifts may be affected by the vast functional redundancy of bacterial groups. All bacterial communities, including those at reference sites, were highly dynamic. Respiration studies of amended sediments indicated that fish farm sediments were at least as resilient and diverse as reference site communities. The results of this study indicate that the functional redundancy of highly complex bacterial communities contributes to their robustness. The relationship between diversity and stability in bacterial communities remains unclear and requires further investigation before an understanding of bacterial response to perturbation is possible.

Advective relief of CO 2 limitation in microphytobenthos in highly productive sandy sediments - Perran L. M. Cook; Hans Røy (Limnology and Oceanography, 2006)
Following field observations of increased photosynthesis at increased rates of sediment flushing in sandy sediments, we conducted a series of laboratory experiments to elucidate the mechanism behind these observations. Column experiments in which water was pumped though sand at rates ranging from 0 to 613 L m −2 d −1 showed that carbon (C) fixation, as measured using carbon‐14 ( 14 C) incorporation, increased from 6.4 to 8.6 mmol m −2 h −1 with increasing rates of flushing. Bottle incubations showed that the addition of inorganic nutrients [ammonium ion (NH 4 + ), inorganic phosphate (HPO 4 − ), silicic acid Si(OH) 4 ] did not stimulate C fixation over short‐term incubations. Microprofiles of pH showed that the pH within the photic zone increased to 8.9, reducing free carbon dioxide (CO 2 ) concentrations to ~0.5 µmol L −1 . Further bottle incubations, where pH and total inorganic carbon (TCO 2 ) were manipulated, showed that high pH (9.6) did not affect photosynthesis if free CO 2 was present at concentrations of 10 µmol L −1 , suggesting a direct effect of low free CO 2 concentrations. 14 C fixation profiles at a resolution of 100 µm recorded by b‐radiation imaging showed that while the depth specific maximum rates of C fixation were the same under both diffusive and advective (flushed) conditions, the integrated rates of photosynthesis were highest under flushed conditions because of a thickening of the photosynthetic zone. We conclude that advective pore‐water transport can enhance benthic photosynthesis in shallow permeable sand sediments by counteracting CO 2 limitation.